A new function of copper zinc superoxide dismutase: as a regulatory DNA-binding protein in gene expression in response to intracellular hydrogen peroxide. Issue 10 (9th April 2019) - Li, Xiang; Qiu, Shuang; Shi, Jiayuan; Wang, Shanshan; Wang, Mingfang; Xu, Yulin; Nie, Zefeng; Liu, Chunrong; Liu, Changlin
Abstract: In microorganisms, a number of metalloproteins including PerR are found to regulate gene expression in response to environmental reactive oxygen species (ROS) changes. However, discovery of similar regulatory mechanisms remains elusive within mammalian cells. As an antioxidant metalloenzyme that maintains intracellular ROS homeostasis, copper zinc superoxide dismutase (SOD1) has high affinity for DNA in solution and in cells. Here, we explored the regulatory roles of SOD1 in the expression of genes in response to ROS changes within mammalian cells. SOD1-occupied DNA sites with distinct sequence preference were identified. Changing ROS levels both were found to impact DNA–SOD1 interactions in solution and within HeLa cells. GGA was one of the base triplets that had direct contact with SOD1. DNA–SOD1 interactions were observed to regulate the ROS-responsive expression of functional genes including oncogenes and amyotrophic lateral sclerosis-linked genes in transcriptional phases. Our results confirm another function of SOD1, acting as a H2 O2 -responsive regulatory protein in the expression of numerous mammalian genes.